Total synthesis of pyrrolo[2,3-c]quinoline alkaloid: trigonoine B - Nishiyama, Takashi; Hamada, Erina; Ishii, Daishi; Kihara, Yuuto; Choshi, Nanase; Nakanishi, Natsumi; Murakami, Mari; Taninaka, Kimiko; Hatae, Noriyuki; Choshi, Tominari (Beilstein Journal of Organic Chemistry, 2021)
The first total synthesis of the pyrrolo[2,3-c]quinoline alkaloid trigonoine B (1) was accomplished via a six-step sequence involving the construction of an N-substituted 4-aminopyrrolo[2,3-c]quinoline framework via electrocyclization of 2-(pyrrol-3-yl)benzene containing a carbodiimide moiety as a 2-azahexatriene system. The employed six-step sequence afforded trigonoine B (1) in 9.2% overall yield. The described route could be employed for the preparation of various N-substituted 4-aminopyrroloquinolines with various biological activities.
Keywords: 2-azahexatiriene system; carbodiimide; electrocyclization; pyrrolo[2,3-c]quinoline; trigonoine B

(untitled) - Li, S.-F.; Di, Y.-T.; He, H.-P.; Zhang, Y.; Wang, Y.-H.; Yin, J.-L.; Tan, C.-J.; Li, S.-L.; Hao, X.-J. (Tetrahedron Lett., 2011)

(untitled) - Carroll, A. R.; Duffy, S.; Avery, V. M. (J. Org. Chem., 2010)

(untitled) - Sangnoi, Y.; Sakulkeo, O.; Yuenyongsawad, S.; Kanjana-opas, A.; Ingkaninan, K.; Plubrukarn, A.; Suwanborirux, K. (Mar. Drugs, 2008)

(untitled) - Okanya, P. W.; Mohr, K. I.; Gerth, K.; Jansen, R.; Müller, R. (J. Nat. Prod., 2011)

(untitled) - Ni, L.; Li, Z.; Wu, F.; Xu, J.; Wu, X.; Kong, L.; Yao, H. (Tetrahedron Lett., 2012)

(untitled) - Schwalm, C. S.; Correia, C. R. D. (Tetrahedron Lett., 2012)

(untitled) - Ma, X.; Vo, Y.; Banwell, M. G.; Willis, A. C. (Asian J. Org. Chem., 2012)

(untitled) - Lindsay, A. C.; Sperry, J. (Synlett, 2013)

(untitled) - Aguiar, A. C. C.; Panciera, M.; Simão dos Santos, E. F.; Singh, M. K.; Garcia, M. L.; de Souza, G. E.; Nakabashi, M.; Costa, J. L.; Garcia, C. R. S.; Oliva, G.; Correia, C. R. D.; Guido, R. V. C. (J. Med. Chem., 2018)

(untitled) - Mahajan, J. P.; Suryawanshi, Y. R.; Mhaske, S. B. (Org. Lett., 2012)

(untitled) - Yamaoka, Y.; Yoshida, T.; Shinozaki, M.; Yamada, K.-i.; Takasu, K. (J. Org. Chem., 2015)

(untitled) - Bolte, B.; Bryan, C. S.; Sharp, P. P.; Sayyahi, S.; Rihouey, C.; Kendrick, A.; Lan, P.; Banwell, M. G.; Jackson, C. J.; Fraser, N. J.; Willis, A. C.; Ward, J. S. (J. Org. Chem., 2020)

(untitled) - Panarese, J. D.; Lindsley, C. W. (Org. Lett., 2012)

(untitled) - Choshi, T.; Hibino, S. (Heterocycles, 2011)

(untitled) - Hibino, S. (Yakugaku Zasshi, 2016)
and related references cited.

(untitled) - Furukawa, Y.; Sawamoto, A.; Yamaoka, M.; Nakaya, M.; Hieda, Y.; Choshi, T.; Hatae, N.; Okuyama, S.; Nakajima, M.; Hibino, S. (Molecules, 2019)

(untitled) - Itoh, T.; Hatae, N.; Nishiyama, T.; Choshi, T.; Hibino, S.; Yoshimura, T.; Ishikura, M. (Med. Chem. Res., 2018)

(untitled) - Nishiyama, T.; Hatae, N.; Mizutani, M.; Yoshimura, T.; Kitamura, T.; Miyano, M.; Fujii, M.; Satsuki, N.; Ishikura, M.; Hibino, S.; Choshi, T. (Eur. J. Med. Chem., 2017)

(untitled) - Hayashi, K.; Choshi, T.; Chikaraishi, K.; Oda, A.; Yoshinaga, R.; Hatae, N.; Ishikura, M.; Hibino, S. (Tetrahedron, 2012)

(untitled) - Nishiyama, T.; Hatae, N.; Chikaraishi, K.; Uchida, K.; Yokoyama, C.; Hibino, S.; Choshi, T. (Heterocycles, 2019)

(untitled) - Choshi, T.; Yamada, S.; Sugino, E.; Kuwada, T.; Hibino, S. (J. Org. Chem., 1995)

(untitled) - Choshi, T.; Yamada, S.; Sugino, E.; Kuwada, T.; Hibino, S. (Synlett, 1995)

(untitled) - Choshi, T.; Tonari, A.; Yoshioka, H.; Harada, K.; Sugino, E.; Hibino, S. (J. Org. Chem., 1993)

(untitled) - Yoshioka, H.; Matsuya, Y.; Choshi, T.; Sugino, E.; Hibino, S. (Chem. Pharm. Bull., 1996)

(untitled) - Nishiyama, T.; Murakami, M.; Taninaka, K.; Hamada, E.; Endo, M.; Kinou, D.; Hatae, N.; Choshi, T. (Heterocycles, 2021)

(untitled) - Tsukano, C.; Nakajima, M.; Hande, S. M.; Takemoto, Y. (Org. Biomol. Chem., 2019)

(untitled) - Molina, P.; Fresneda, P. M.; Alarcón, P. (Tetrahedron Lett., 1988)

(untitled) - Hibino, S.; Sugino, E.; Kuwada, T.; Ogura, N.; Shintani, Y.; Satoh, K. (Chem. Pharm. Bull., 1991)

(untitled) - Morrison, M. D.; Hanthorn, J. J.; Pratt, D. A. (Org. Lett., 2009)

(untitled) - Harada, R.; Nishida, N.; Uchiito, S.; Onozaki, Y.; Kurono, N.; Senboku, H.; Masao, T.; Ohkuma, T.; Orito, K. (Eur. J. Org. Chem., 2012)

(untitled) - Wetzel, A.; Gagosz, F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Nakanishi, M.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Bonvin, Y.; Callens, E.; Larrosa, I.; Henderson, D. A.; Oldham, J.; Burton, A. J.; Barrett, A. G. M. (Org. Lett., 2005)

(untitled) - Wu, S.; Liu, C.; Luo, G.; Jin, Z.; Zheng, P.; Chi, Y. R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Silva, S. B. L.; Della Torre, A.; de Carvalho, J. E.; Ruiz, A. L. T. G.; Silva, L. F., Jr (Molecules, 2015)